An Assistance of Islamic University EFL Students through Artificial Intelligence (AI) Machine Translation and Writing Tools - Suhono, Suhono (International Journal of Community Engagement Payungi, 2023)
Integrating Artificial Intelligence (AI) into language learning has transformed traditional educational paradigms, particularly in the context of English language acquisition among Islamic university students. This research aimed to assist Islamic university EFL students at Metro Lampung in using AI, especially machine translation and AI writing tools. The method used Participatory   Action   Research (PAR). PAR can act as a framework that facilitates collaboration between technology developers (AI) and English language learners. This assistance gave an impact for Islamic university EFL students. Using AI writing tools such as Grammarly presents many advantages for students, encompassing the refinement of grammatical precision and the fostering of autonomous writing skills. The merits considerably surpass the drawbacks when these tools are judiciously incorporated into the educational process. As students navigate the complexities of academic writing, the support of AI can serve as a conduit to heightened proficiency and self-assurance in their communicative abilities.  Moreover, assistance through Machine Translation, such as DeepL, emerges as an essential resource for students navigating the intricacies of multilingual academic landscapes. Its sophisticated technology, intuitive interface, and capacity for ongoing enhancement render it indispensable for improving comprehension and facilitating effective communication. The support it offers signifies a substantial progression in the domain of language translation, harnessing the potential of deep learning technology to provide superior-quality translations.